Handbook of research on contemporary theoretical models in information systems - Dwivedi, Yogesh K.; Lal, Banita; Williams, Michael D.; Schneberger, Scott L.; Wade, Michael (Information Science Reference, 2009)
"This book provides a comprehensive understanding and coverage of the various theories, models and related research approaches used within IS research" - Provided by publisher
Literaturverz. S. 563 - 639
Keywords: Information technology -- Research; Theorie; Modell; Forschung; Informationssystem; Aufsatzsammlung